Program Sveta Evrope HELP v slovenskem sodstvu - Đorđević, Miodrag (Podjetje in delo, 2020)
The emphasis in the protection of human rights is not on their declaration in the ECHR, but on their implementation and thus the effectiveness of the legal protection provided by the courts. It is therefore important to strengthen the knowledge and professional skills of judges. Continuing education and training is the basic professional standard of a judge and a measure of their attitude towards the judicial mission. Continuing education of judges is not only the right of judges, but also our duty. On the other hand, it is also the right of citizens to a trial within a reasonable time, to fairly conducted procedure, to quality, well-considered and professionally substantiated/reasoned decisions. Expertise and quality court decisions are what strengthen the integrity of the judge, the judiciary and thus the rule of law.
Keywords: človekove pravice; EKČP; ESČP; HELP (izobraževanje o človekovih pravicah za pravne strokovnjake); izobraževanje; neposredna uporaba EKČP; spletni tečaji; učinkovito pravno varstvo; usposabljanje; vezanost na ustavo in zakon